Brooding behaviour and influence of moon cycle on chick provisioning in a pelagic seabird, the Bulwer’s petrel (Bulweria bulwerii) - Pinto, Maria Gomes Ribeiro Teixeira, 1989- (2013)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2013